Development of breadfruit flour (Artocarpus altilis) with the addition of gelatine as a potential edible film - Khairol Nadia, A.H.; Russly, A.R.; Nur Hanani, Z.A. (Rynnye Lyan Resources, 2024)
The potential application of biodegradable films for food applications has gained interest as an alternative to synthetic plastic packaging. Breadfruit is a common starchy fruit in nature and due to its unique and wide availability, it can be good a source for developing biopolymers. This study aimed to develop packaging films made from unripe green breadfruit (Artocarpus altilis) flour with different concentrations of bovine gelatine. The ratios of gelatine and breadfruit flour (G:BF) were 0:5 (G0), 1:5 (G2), 2:5 (G4), 3: 5(G6), 4:5 (G8) and 5:5 (G10). The physical, mechanical and optical properties of these films were investigated. The findings of this study showed that the addition of bovine gelatine in flour solutions had significantly (P<0.05) improved the film thickness, tensile strength (TS), optical properties and water vapour permeability (WVP). Breadfruit film with no gelatine (control) showed the lowest WVP (P<0.05). Based on the Fourier transform infrared spectroscopy (FTIR) spectra, the chemical interaction of hydroxyl group from gelatine and the carboxyl group of breadfruit flour occurred. Therefore, gelatine helped to improve the water barrier and mechanical properties of the BF films as supported by the scanning electron microscopy (SEM) images. Further study to enhance film properties is necessary to apply the material to food products.